Fuzzy Models in Measuring Competitiveness of Agroindustry - Adzic, Sofija; Stojic, Dragan (Industrija, 2014)
Competitiveness has become over the past three decades, an integral part of modern management and business development. The authors observe 18 enterprises in Vojvodina in the period 2009-2013 from Agriculture and Manufacturing sectors and measure their competitiveness based on the involvement of intellectual capital. Authors also propose the construction of a portfolio by solving the multiple criteria optimization problem. Fuzzy methodology has been applied: yields are modeled with trapezoidal fuzzy numbers, and the risk is measured by semi-deviation. Results of the study indicate a deviation from the Markowitz model which assumes that the yields are normally distributed, and that the appropriate risk measure is the variance of returns. Portfolios obtained by fuzzy methodology are characterized by higher values of intellectual capital, when compared to its counterparts obtained from Markowitz optimization.